Lipid and brain volumetric measures in multiple sclerosis patients: findings from a large observational study - Lorincz, Balazs; Vrablik, Michal; Murali, Ramanathan; Havrdova, Eva Kubala; Horakova, Dana; Krasensky, Jan; Vaneckova, Manuela; Uher, Tomas (Acta neurologica Belgica, 2024)
OBJECTIVES: This study aimed to investigate relationships between cholesterol profile, brain volumetric MRI, and clinical measures in a large observational cohort of multiple sclerosis (MS) patients. MATERIALS AND METHODS: We included 1.505 patients with 4.966 time points including complete lipid, clinical, and imaging data. The time among lipid, brain MRI and clinical measures was under 90 days. Cross-sectional statistical analysis at baseline was performed using an adjusted linear regression and analysis of longitudinal lipid and MRI measures data was performed using adjusted linear mixed models. RESULTS: We found associations between higher high-density lipoprotein cholesterol (HDL-C) and lower brain parenchymal fraction (BPF) at cross-sectional analysis at baseline (B = -0.43, CI 95%: -0.73, -0.12, p = 0.005), as well as in longitudinal analysis over follow-up (B = -0.32 ± 0.072, χ2 = 36.6; p = < 0.001). Higher HDL-C was also associated with higher T2-lesion volume in longitudinal analysis (B = 0.11 ± 0.023; χ2 = 23.04; p = < 0.001). We observed a weak negative association between low-density lipoprotein cholesterol (LDL-C) levels and BPF at baseline (B = -0.26, CI 95%: -0.4, -0.11, p = < 0.001) as well as in longitudinal analysis (B = -0.06 ± 0.03, χ2 = 4.46; p = 0.03). T2-LV did not show an association with LDL-C. We did not find any association between lipid measures and disability. The effect of lipid levels on MRI measures and disability was minimal (Cohen f2 < 0.02). CONCLUSIONS: Our results contradict the previously described exclusively positive effect of HDL-C on brain atrophy in patients with MS. Higher LDL-C was weakly associated with higher brain atrophy but not with higher lesion burden.
Keywords: Cholesterol; lidé; magnetická rezonanční tomografie; Adult; Middle Aged; Multiple sclerosis; cholesterol; Magnetic Resonance Imaging; LDL; Multiple Sclerosis; MRI; LDL-cholesterol; Female; Longitudinal Studies; HDL; Humans; průřezové studie; Cross-Sectional Studies; roztroušená skleróza; Lipid; lidé středního věku; kohortové studie; Cohort Studies; mužské pohlaví; Cholesterol, LDL; HDL-cholesterol; ženské pohlaví; Cholesterol, HDL; Male; longitudinální studie; mozek; Brain; Brain atrophy; Lesion volume; dospělí